EVOH functionalized PE battery separator as the porous substrate for TFC organic solvent nanofiltration membranes - Guoke Zhao; Tian Zhong; Xinkai Li; Hao Yu; Guoyuan Pan; Yang Zhang; Yiqun Liu (Advanced Membranes)
Scholarly discourse surrounding the thin film composite organic solvent nanofiltration (TFC OSN) membrane field has largely been dominated by focusing on the optimization of the selective layer. However, this often leaves the porous support layer, with its innate solvent resistance, cost-effectiveness, and superior permeability, in the shadows. This study presents a novel OSN membrane utilizing a polyethylene (PE) battery separator as the porous substrate. The structural affinity between ethylene-vinyl alcohol and PE facilitates efficient hydrophilic modification, which allows for uniform and compact polyamide selective layer formation through interfacial polymerization. The HPE-NF-1.0 membrane exhibits rejections of 99.5 ​%, 96.7 ​%, 100 ​%, and 97.2 ​% for Methyl Orange, Rhodamine B, Congo red, and Rose Bengal, respectively. It also shows a solvent flux of 52.5 LMH in methanol and robust resistance against alcoholic solvents and DMF. Using PE as the porous substrate, we bypass intricate and time-demanding cross-linking processes and complex pore-preservation post-treatments, providing a simplified strategy for TFC OSN membrane fabrication.